'I'm less intolerant': Reflexive self-assessment in religious education - Fancourt, N (2010)
This article describes practitioner research which shows how self-assessment as a form of assessment for learning can be aligned with all the educational goals of religious education in England, notably the self-assessment of attitudes and values, such as tolerance and respect. The background literature on assessment for learning is described, as well as the literature on reflection in religious education, notably 'learning from religion'. Practitioner research with Year 9 pupils in a monocultural comprehensive school is described. The analysis shows how pupils are able to reflect on their development in: knowledge and understanding; evaluation and reflection; and attitudes and values. Reflexive self-assessment is defined, drawing on social science descriptions of reflexivity, both in the light of assessment for learning and interpretive approaches to religious education. The implications of this for policy and practice are considered. © 2010 Christian Education.